2017
DOI: 10.3847/2041-8213/aa9d82
|View full text |Cite
|
Sign up to set email alerts
|

How Many Kilonovae Can Be Found in Past, Present, and Future Survey Data Sets?

Abstract: The discovery of a kilonova (KN) associated with the Advanced LIGO (aLIGO)/Virgo event GW170817 opens up new avenues of multi-messenger astrophysics. Here, using realistic simulations, we provide estimates of the number of KNe that could be found in data from past, present, and future surveys without a gravitational-wave trigger. For the simulation, we construct a spectral time-series model based on the DES-GW multi-band light curve from the single known KN event, and we use an average of BNS rates from past s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 44 publications
4
80
1
Order By: Relevance
“…Using a single SED time-series model to describe GW170817, Scolnic et al (2018a) simulated KN rates in past, present, and future surveys, including LSST. We expect more diversity than this single event, so for PLAsTiCC we included the set of SED time-series models of BNS mergers from Kasen et al (2017).…”
Section: Technical Details For Knmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a single SED time-series model to describe GW170817, Scolnic et al (2018a) simulated KN rates in past, present, and future surveys, including LSST. We expect more diversity than this single event, so for PLAsTiCC we included the set of SED time-series models of BNS mergers from Kasen et al (2017).…”
Section: Technical Details For Knmentioning
confidence: 99%
“…A volumetric KN rate of 1×10 −6 yr −1 Mpc −3 is estimated in Scolnic et al (2018a) based on a compilation of rates in Abbott et al (2016). For PLAsTiCC, we increased this rate by a factor of 6 for two reasons: to provide a sufficient training set (∼100), and to reduce the Kaggle score change from correctly identifying each KN.…”
Section: Rate Modelmentioning
confidence: 99%
“…Future analyses may also use photometric classification methods, including DL, for the identification of transients 27,28 . The possibility of serendipitous kilonovae discovery using this approach in wide-field surveys such as LSST have been discussed in REFs 29,30 .…”
Section: Identification Of Optical Counterpartsmentioning
confidence: 99%
“…We build on the works of Rosswog et al (2017); Scolnic et al (2017) in several ways. We consider the ability of LSST to serendipitously detect kNe but with the eventual aim of using these detections as triggers to search catalogues of GW data to find sub-threshold GW events.…”
mentioning
confidence: 99%
“…3.1. Following Scolnic et al (2017), we consider the case where all BNS kNe are represented by the observed spectral energy distribution (SED) evolution of GW170817. We additionally consider a physically-motivated population model of BNS kNe and, for the first time, consider a population model of NSBH kNe.…”
mentioning
confidence: 99%